Sedimentary response to tectonic uplift of the Dukla basin margin recorded at Skrzydlna – the Menilite Beds (Oligocene), Outer Carpathians, S Poland - Siemińska, Aneta; Starzec, Krzysztof; Godlewski, Paweł; Wendorff, Marek (Geology, Geophysics and Environment, 2018)
The Menilite Beds (Oligocene of Polish Flysch Carpathians) at Skrzydlna crops out in a structurally complex zone of the Fore-Magura Unit, which is tectonically overridden by Magura Nappe thrust form the S. The exposed sedimentary suite, representing the Dukla Basin, consists of fine-grained, well organised strata deposited in a low-energy, deep marine basin, which are abruptly overlain by poorly organised, coarse sandy conglomerate that forms a Mass Transport Deposit (MTD) complex. The MTD contains large boulders of extrabasinal rocks, massive sandstone beds with intrabasinal mudstone clasts, and slump sheets of sandstones. Above rests a fining- upwards sequence of sandstone beds interlayered with mudstones. The fine-grained facies reappear above to terminate the exposed succession. Erosional contacts and rapid facies changes, both vertical and lateral, are characteristic for the MTD unit. The sandstone-mudstone unit above contains laterally migrating erosional channels filled with massive sandy conglomerate in the lower part. Turbidites of varying density and completeness of internal structures that occur above are accompanied by an association of mixed facies including large-scale dune cross-bedding.Mineralogically, the sandstones are quartz arenites, sub-lithic arenites and wackes. Calcarenite grains – bioclasts, micrite and marl occur in substantial proportions only in the uppermost part of the succession. The point-counting data plotted on Qm-F-Lt diagram are clustered within the recycled fields: quartzose and transitional. Mineralogical maturity of the sandstones has the tendency to decrease from the sub-MTD strata upwards via the MTD unit to the lower part of the sandstone-mudstone complex; then it increases to the youngest sandstone beds with carbonate grains. These tendencies, associated with sedimentary features of the succession, reflect rapid uplift, emergence and progressive erosion of the terrigenous detritus source area, followed by tectonic stabilisation reflected by the appearance of the “carbonate factory”.